Exploring Language Learning Tasks in Synchronous Computer-mediated Communication (SCMC) - Nik Aloesnita, Nik Mohd Alwi (2011)
Research has shown that learner-learner interaction during task-based, online text chat increases learner participations, reduces anxiety level and promotes learner attention to language form while communicating meaning (Smith, 2008; Sotillo, 2005). Therefore, language learners should be given the opportunities to communicate with each other and to work collaboratively using appropriate materials in the online text chat setting. Relatively little research in the context of engineering, technical or science students doing language courses (e.g. Nik, 2010) has investigated how engineering-based tasks are used in online text chat may influence language learning opportunities during task performance. This is particularly important because engineering jobs increasingly require electronic communication (Lee & Yeap, 2005). The data gathered from the text chat transcripts of engineering degree students provide evidence that taskbased text chat interactions to a certain extent may promote attention to language expression and provide language learning opportunities.